2021
DOI: 10.1001/jama.2021.0694
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Intravenous Immunoglobulins Plus Methylprednisolone vs Immunoglobulins Alone With Course of Fever in Multisystem Inflammatory Syndrome in Children

Abstract: Key PointsQuestionIs there an association between treatment with intravenous immunoglobulins (IVIG) plus methylprednisolone vs IVIG alone and course of fever in multisystem inflammatory syndrome in children (MIS-C) associated with severe acute respiratory syndrome coronavirus 2?FindingsThis retrospective cohort study included 111 children with MIS-C. After propensity score matching, the rate of treatment failure (defined by the persistence of fever 2 days after the introduction of first-line therapy or recrude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
283
7
30

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(343 citation statements)
references
References 33 publications
23
283
7
30
Order By: Relevance
“…Although it is rare, MIS-C is a critical diagnosis to consider in any child with fever, evidence of inflammation, and organ dysfunction where covid-19 is endemic. 29 Prompt treatment with intravenous immunoglobulin and steroids can reduce the inflammatory response and may improve outcomes.…”
Section: Multisystem Inflammatory Disease In Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is rare, MIS-C is a critical diagnosis to consider in any child with fever, evidence of inflammation, and organ dysfunction where covid-19 is endemic. 29 Prompt treatment with intravenous immunoglobulin and steroids can reduce the inflammatory response and may improve outcomes.…”
Section: Multisystem Inflammatory Disease In Childrenmentioning
confidence: 99%
“…A May 2020 systematic review from 26 countries reported a MIS-C incidence of 0.14% among all children with SARS-CoV-2 infection,1 but this estimated incidence may be imprecise because of potential underestimation of overall SARS-CoV-2 infections in children. Although it is rare, MIS-C is a critical diagnosis to consider in any child with fever, evidence of inflammation, and organ dysfunction where covid-19 is endemic 29. Prompt treatment with intravenous immunoglobulin and steroids can reduce the inflammatory response and may improve outcomes.…”
Section: Multisystem Inflammatory Disease In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Both glucocorticoids and intravenous immunoglobulin (IVIG) are considered the most common first line treatment modalities for immunomodulatory treatment in MIS-C 5 . Although there is minimal research on the efficacy of IVIG and glucocorticoids in combination when compared with IVIG or glucocorticoids alone, a recent retrospective cohort study found that the combination of IVIG with glucocorticoids demonstrated a more favorable fever course than IVIG alone 7 . Respondents in a recent international survey reported steroid use most often in patients with severe clinical presentation (64%) 6 .…”
Section: Treatmentmentioning
confidence: 99%
“…The benefits of IVIG are debatable, but several studies have not determined the pre-existing antiviral potency of the same [191][192][193][194][195]. Such studies do not preclude the potential benefit of IVIG in other niche situations, such as immune thrombocytopenia, ascending polyneuropathy, or multisystem inflammatory disorder attributable to COVID-19 [196][197][198]. On this theme, however, there is yet potential for the creation of IVIG specifically from donors with convalescent COVID-19 infection.…”
Section: Human Trials Of Passive Immunitymentioning
confidence: 99%